Algorithmic Literacy and the Role for Libraries - Ridley, Michael; Pawlick-Potts, Danica (Information technology and libraries, 2021)
Artificial intelligence (AI) is powerful, complex, ubiquitous, often opaque, sometimes invisible, and increasingly consequential in our everyday lives. Navigating the effects of AI as well as utilizing it in a responsible way requires a level of awareness, understanding, and skill that is not provided by current digital literacy or information literacy regimes. Algorithmic literacy addresses these gaps. In arguing for a role for libraries in algorithmic literacy, the authors provide a working definition, a pressing need, a pedagogical strategy, and two specific contributions that are unique to libraries.